2018
DOI: 10.1001/jamainternmed.2017.7299
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable Risk Factors and Prevention of Dementia

Abstract: In 2017, the International Diabetes Federation (IDF) estimated that 451 million people were diabetic and will exceed 690 million by 2045. 12

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 107 publications
0
57
0
1
Order By: Relevance
“…However, longitudinal studies showed that up to 50% of patients with MCI at their first doctor visit returned to normal at follow-up examinations (Larrieu et al, 2002;Ganguli et al, 2004), particularly in population-based cohorts. Apart from neurodegenerative disorders, many factors affect cognitive performance in older populations, including age, gender, education, vascular risk factors, genetic background, hormonal changes, and comorbidities (Yaffe, 2018). Additionally, studies of MCI differed greatly as to their inclusion criteria, study settings, sample characteristics, classification and subtype of MCI, observation period, and evaluation of cognitive and other relevant features.…”
Section: Introductionmentioning
confidence: 99%
“…However, longitudinal studies showed that up to 50% of patients with MCI at their first doctor visit returned to normal at follow-up examinations (Larrieu et al, 2002;Ganguli et al, 2004), particularly in population-based cohorts. Apart from neurodegenerative disorders, many factors affect cognitive performance in older populations, including age, gender, education, vascular risk factors, genetic background, hormonal changes, and comorbidities (Yaffe, 2018). Additionally, studies of MCI differed greatly as to their inclusion criteria, study settings, sample characteristics, classification and subtype of MCI, observation period, and evaluation of cognitive and other relevant features.…”
Section: Introductionmentioning
confidence: 99%
“…A steep increase in the prevalence of dementia is expected [1], associated with social, economic, and societal challenges. Early detection of dementia is crucial for an implementation of therapeutic strategies in the earliest disease stages [2], and reliable cognitive screening tools play an important role in this process of identifying individuals with cognitive impairment [3]. In the context of clinical research, accurate cognitive assessment tools are needed for an adequate selection of participants, since erroneous inclusion or exclusion of individuals may bias study findings [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Although the impact of these factors varies at different life stages, eliminating them at any stage would be beneficial. Moreover, studies recommend active treatment and intervention of modifiable dementia risk factors, which would potentially delay or prevent 30% of dementia cases [1], [4].…”
Section: A Dementia Risk Factorsmentioning
confidence: 99%
“…www.ijacsa.thesai.org Risk factors for dementia can be either modifiable or nonmodifiable [3]. Fortunately, dementia could be delayed or possibly prevented by eliminating some of its modifiable risk factors [4].…”
Section: Introductionmentioning
confidence: 99%